Exosomes for Intramyocardial Intercellular Communication - Elisabetta Cervio; Lucio Barile; Tiziano Moccetti; Giuseppe Vassalli (Stem Cells International)
Cross-talk between different cell types plays central roles both in cardiac homeostasis and in adaptive responses of the heart to stress. Cardiomyocytes (CMs) send biological messages to the other cell types present in the heart including endothelial cells (ECs) and fibroblasts. In turn, CMs receive messages from these cells. Recent evidence has now established that exosomes, nanosized secreted extracellular vesicles, are crucial mediators of such messages. CMs, ECs, cardiac fibroblasts, and cardiac progenitor cells (CPCs) release exosomes carrying nonrandom subsets of proteins, lipids, and nucleic acids present in their cells of origin. Exosomes secreted from CMs are internalized by fibroblasts and regulate gene expression in these cells as well as in ECs. CPC-derived exosomes protect CMs against apoptosis while also stimulating angiogenesis. They are rich in cardioprotective and proangiogenic microRNAs such as miR-146, miR-210, and miR-132. When injected into infracted hearts in vivo, CPC-derived exosomes reduce infarct size and improve cardiac function. Thus, exosomes are emerging both as key mediators of intercellular communication in the heart and as therapeutic candidates for heart disease.